Cancelling Copyrights - Lauriat, Barbara; Brauneis, Robert (The Columbia Journal of Law & the Arts, 2026)
In the United States, registering a claim of copyright in a work of authorship is easy. Cancelling an existing copyright registration is not. This is a problem that requires attention. This Article makes those three important points and suggests what should be done. U.S. copyright registration confers important benefits and legal protections on copyright owners. In any intellectual property regime with registered rights, mechanisms for correcting the record and removing rights granted in error are integral components of a functional system. While courts have the power to cancel invalid trademark registrations and patents, they do not have the power to cancel invalid copyright registrations, and the Copyright Office has no process that would allow third parties to challenge existing registrations. Copyright registrations may only be cancelled at the discretion of the Register of Copyrights. Consequently, few registrations are ever cancelled. In this Article, we show that the lack of procedures for cancelling copyright registrations has contributed to an improperly high level of inaccuracy and error on the registry. This situation compromises a fundamental purpose of the registration system and has the potential to cause real harm. Using specific case examples and an empirical study of cancellation data from the Copyright Office, we demonstrate how and why the current mechanisms for correcting the registration record at the Copyright Office are inadequate. Finally, we recommend a series of legal and practical changes that would enable registration and recordation to serve their principal aims of providing accurate information and clearing title to support markets in works of authorship.